2015
DOI: 10.1002/cjce.22189
|View full text |Cite
|
Sign up to set email alerts
|

Re‐examining the influence of chloride ions on electrochemical CO2 corrosion of pipeline steels—corrosion of the heat‐affected zones (HAZs) of API‐X100 steel

Abstract: This research investigates the corrosion characteristics of simulated heat‐affected zones (HAZs) of API X‐100 pipeline steels in CO2‐saturated brines of different chloride concentrations. It links the significances of the HAZ microstructure and chloride concentration to the corrosion kinetics and corrosion products. The ferritic HAZs dissolve at almost two times the rate of acicular ferritic and bainitic HAZs. This paper shows that the samples corrode at rates increasing with the chloride concentration to a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The corrosion process may be dominated by the three reactions, Eqs. – : Fe2++CO32FeCO3 Fe2++2HCO3Fetrue(normalHnormalCO3true)2 Fe(HCnormalO3)2FeCO3+CO2+normalH2O …”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion process may be dominated by the three reactions, Eqs. – : Fe2++CO32FeCO3 Fe2++2HCO3Fetrue(normalHnormalCO3true)2 Fe(HCnormalO3)2FeCO3+CO2+normalH2O …”
Section: Analysis and Discussionmentioning
confidence: 99%
“…What is more, Fe 2+ can react with CO 3 2− via a one-stage reaction with carbonate, or via a two-stage reaction with bicarbonate. [19][20][21][22] The corrosion process may be dominated by the three reactions, Eqs. (7)-(9) [19,20,22] :…”
Section: Failure Mechanismmentioning
confidence: 99%
“…It might not have fully consolidated some of the mechanistic details that are until today being investigated, but it provides a visual guide that helps better understand the corrosion reactions and the significance of the properties and reactivity of the corrosion products. The test samples are made of API-X100, a new-generation pipeline steel, whose electrochemical significance and behavior were explained and examined previously ( Ref 1,8,10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Hausler et al demonstrated that Cl − had no noteworthy effect on CO 2 corrosion. However, Eliyan revealed that corrosion reactions exhibited a special trend with chloride concentration, as they increased and later decreased due to the thickening of corrosion products. Liu found that for carbon steel, Cl − had no effect on the composition of the corrosion product.…”
Section: Introductionmentioning
confidence: 99%